Erratum - Anghel, Ion; Enache, Calcedonia; Merino, Fernando (Journal of Business Economics and Management, 2020)
The article “Macroeconomic determinants of corporate failures. Evidence from Romania and Spain” by Ion Anghel, Calcedonia Enache, Fernando Merino published in Journal of Business Economics and Management, 21(3), 743–759, https://doi.org/10.3846/jbem.2020.12217, contained the following errors: • Some information in the 5th graph about Jmax was not given in Table 2, page 752. • Information for Spain should be added in Figures 2 and 3 in page 753. • Some results in Table 4 should be presented in bold in page 754. These have been corrected. The publisher and the authors Ion Anghel, Calcedonia Enache, Fernando Merino apologise for the errors.